Assignment of the Absolute Configuration of (+)-Diplopyrone, the Main Phytotoxin Produced by Diplodia mutila, the Pathogen of the Cork Oak Decline, by a Nonempirical Analysis of Its Chiroptical Properties† - Giorgio, Egidio; Maddau, Lucia; Spanu, Emanuela; Evidente, Antonio; Rosini, Carlo (The Journal of Organic Chemistry, 2004)
The nonempirical assignment of the absolute configuration of (+)-diplopyrone, the main phytotoxin of Diplodia mutila, i.e., an endophytic fungus, widespread in Sardinian oak forests, and considered one of the main causes of cork oak decline, has been approached by two different methods:? (a) the exciton analysis of the circular dichroism (CD) spectrum and (b) the ab initio calculation of the optical rotatory power. Both methods indicate that (+)-diplopyrone is 6-[(1S)-1-hydroxyethyl]-2,4a(S),6(R),8a(S)-tetrahydropyrano[3,2-b]pyran-2-one, so the stereostructure of this important biomolecule is safely determined for the first time. A comparison of advantages and limitations of the two methods of analysis is also presented.
From Duplicate 2 (Assignment of the Absolute Configuration of (+)-Diplopyrone, the Main Phytotoxin Produced by Diplodia mutila, the Pathogen of the Cork Oak Decline, by a Nonempirical Analysis of Its Chiroptical Properties† - Giorgio, Egidio; Maddau, Lucia; Spanu, Emanuela; Evidente, Antonio; Rosini, Carlo)
Keywords: absolute configuration; Circular dichroism; DeVoe method; diplopyrone (voyant); Mitosporic Fungi; Mitosporic Fungi: pathogenicity; Models; Molecular; Molecular Structure; mycotoxins; Mycotoxins: chemistry; Optical rotation; Plant Diseases; Plant Diseases: microbiology; Pyrones; Pyrones: chemistry; Stereoisomerism